A highly transparent and autonomic self-healing organogel from solvent regulation based on hydrazide derivatives. Issue 34 (15th August 2018) - He, Liu; Ran, Xia; Li, Jinxing; Gao, Qiongqiong; Kuang, Yanmin; Guo, Lijun
Abstract : A solvent-regulated BNB-t4 organogel demonstrates a high transparency and a great self-healing ability. Abstract : Herein, we report a systematic investigation of the solvent-regulated gelation behaviour, self-healing ability and intermolecular interaction mechanism of an azobenzene derivative bearing a hydrazide group, N -(3, 4, 5-tributoxyphenyl)- N ′-4-[(4-hydroxyphenyl)azophenyl] benzohydrazide (BNB-t4). From the gelation studies of BNB-t n ( n = 1, 2, 4 and 8) in various single and binary solvents, we found that the BNB-t4 gel in the 50 : 50 chloroform/cyclohexane (TCM/CYH) mixture demonstrates a high transparency, a great self-healing ability with an almost instant repair capability from vigorous stirring or other damage, and application capacities in removing toxic dyes, adhering on solid surfaces and self-supporting. With the introduction of CYH with a weak hydrogen-bonding interaction and nonpolarity, the gelation ability, transparency, viscoelasticity and self-healing properties of the BNB-t4 organogel have been effectively regulated by changing the CYH composition in TCM/CYH mixtures. The temperature dependent transparency and morphology studies indicate that the high transparency of the BNB-t4 gel originates from the aggregate size of nanoscale fibres. Meanwhile, the rheology studies present the mechanical properties of the self-healing organogels, and indicate that the viscoelasticity and stability of the BNB-t4 gel are efficiently improved by introducing a moderate amount of CYH. Furthermore, the spectral results and analysis using Hansen solubility parameters demonstrate that the hydrogen bonding interactions through the amide and hydroxyl groups of BNB-t4 mainly contribute to the regulation of gelation ability and properties, on the premise of a weak polar interaction and moderate dispersion force. Synthetically, the hydrogen-bonding interactions coupled with the π–π stacking interaction through the azobenzene group and van der Waals interactions via alkyl chains are responsible for the regulated self-assembly behaviours and properties of the BNB-t4 gel in TCM/CYH mixtures. The success in achieving the BNB-t4 gel shows an effective strategy to achieve the specific properties of organogels through regulating specific solubility parameters.